THE RELATIONSHIP BETWEEN THE ISLAMIC REPUBLIC OF IRAN AND THE PALESTINIAN HAMAS MOVEMENT AND ITS IMPACT ON THE PALESTINIAN ISSUE (2010-2015) - ALMadani, Ahmed; Muttaqien, Muhamad (PEOPLE: International Journal of Social Sciences, 2018)
The period between 2010 and 2015 is considered one of the most important turning points in the Middle East region in general, especially in the relationship between the Palestinian Hamas movement and the Islamic Republic of Iran at all levels and areas. This period witnessed political changes in the political reality in the region. The Middle East has been through the demise of political systems and the birth of new political systems, which had an impact on the axis of resistance, especially in the relationship between Hamas and the Islamic Republic of Iran. The relationship between Hamas and Iran has been affected by these changes, especially after the events in Syria and Yemen. The independence of the Hamas decision and the failure to comply with Iranian orders has emerged.This paper attempts to examine the decision of Hamas independent of Iran’s orders regarding the changes in the Middle East through Iran’s demand that Hamas participate in current events in Syria and Yemen in favor of a certain party against another party, and what Hamas’s position on Iranian demands is. This paper will be based on the theoretical framework on the theory of international alliance and the nature of the alliance between state and non-state actor. The relationship between Iran and Hamas is an alliance relationship, considering that Hamas is not a state but a non-state actor. The methodology used in this paper is to analyze Iranian behavior toward Hamas, considering that Iran is considered the leader of the resistance alliance against Israel, and to clarify the Hamas’ response to Iranian demands. The researcher found that Iran is exploiting the Palestinian cause to achieve the purely Iranian interests through slogans and speeches to the Arab and Islamic peoples, Iran’s support for Hamas aimed at achieving Iranian interests in the Middle East region and not serving the Palestinian cause. Hamas is trying to maintain the independence of its national decision without interfering in the internal affairs of Arab and Islamic countries.